Risk management and insurance - Harrington, Scott E.; Niehaus, Greg. (Boston, Mass. : McGraw-Hill, 2004)
Provides the general principles of risk management and insurance and provides useful aspects of insurance contracts and the insurance industry. This book provides conceptual analysis and attention to business risk management and public policy issues.
1. Risk and Its Management2. Objectives of Risk Management3. Risk Identification and Measurement4. Pooling Arrangements and Diversification of Risk5. Insurer Ownership, Financial, and Operational Structure6. Insurance Regulation7. Insolvencies, Solvency Ratings,and Solvency Regulation8. Insurance Pricing9. Risk Aversion and Risk Management by Individuals and Corporations10. Insurability of Risk, Contractual Provisions, and Legal Doctrines11. Loss Control12 Legal Liability for Injuries13. Automobile Insurance14. Homeowners Insurance15. Life Insurance and Annuities 16. Employee Benefits: Overview and Group Medical Coverage17. Retirement Plans18. Workers' Compensation and Employee Injuries19. Social Security 20. Corporate Risk Management and Shareholder Wealth 21. Tax, Regulatory, and Accounting Factors Affecting Corporate Risk Management22. Risk Retention/Reduction Decisions 23. Commercial Insurance Contracts 24. Hedging Risk with Derivative Contracts 25. Alternative Risk Transfer 26. Analysis Tools used in Corporate Risk Management27. Enterprise Risk Management: A Case Study28. Corporate Liability to Customers, Third Parties, and Shareholders29. Issues in Liability Risk and It's Management
Includes index.
Keywords: Risk (Insurance); Risk management